Analisis pembelajaran bahasa Indonesia sebagai bahasa kedua di sekolah Pattanakarn Ying Sueksa Thailand - Wiarm Khalikhmadee; Hermanto Hermanto; Riswanda Himawan (Badan Pengembangan dan Pembinaan Bahasa, 2022)
This research was motivated by the existence of Indonesian language learning for Thai students, which took place in Bangkok Thailand. In the learning process, of course, there are problems that hinder student learning because Indonesian language learning is carried out in Thailand. The method used in this research is descriptive qualitative. This study aims to describe the Indonesian language learning process for students in Bangkok, where these students have a mother tongue with Thai and describe the obstacles that exist in the language learning process. The method of collecting data in this research is the method of listening, observation and interviews. The results of this study conclude as follows: 1) The process of learning Indonesian at school by means of; (a) memorize vocabulary (b) read Indonesian texts, and (c) do practice questions. 2) The obstacles experienced in learning Indonesian are; (a) difficulties in pronouncing some letters in Indonesian, (b) students lack confidence in speaking Indonesian, (c) inadequate attitudes and habits of students, (d) students' cultural and language backgrounds. 3) Solutions to overcome obstacles in the learning process, namely: (a) giving students more time to practice, (b) talking to students individually (c) maximizing learning outcomes in class with limited time, (d) simplifying the material and understanding students, and (e) giving more time to students.